Morphological and leaf anatomical studies on Cleistogenes Serotina (L.) Keng (Poaceae) - Nyakas, Antónia; Molnár, Edit (Acta Agraria Debreceniensis, 2001)
The grass species Cleistogenes serotina (L.) Keng, generally found in the mountainous region in Hungary, has been observed in the lowlands of the Great Hungarian Plain in the last few decades. Since its first recent mention in sand habitat as well it, has been found in several locations in the interfluve between the Danube and the Tisza. In certain, sandy grasslands, the invasion of this species is considerable (e.g. near Fülöpháza the area invaded by Cleistogenes increased almost fourfold within six years). The success of invasion on new habitats is related to changes in the characteristics of plants comparatively studied on mountain and sand populations. We studied blades of leaves on different levels (1st, 5th and 10th) and from different biotops. Cuttings were made, with a thickness of 10-12 μm, at the middle of the blades. The cross sections were observed using a light microscope. Digitised images (DigitPlan) and survey data were arranged into a database. The leaf structure is characterised by the kranz anatomy, and a double layered bundle sheath, which is typical of the aspartate type of C4 grasses. There were significant differences only in cross section area and the number of bundles for various ages of the leaves. There were more bundles in the older leaves than in the younger ones. We did not find any difference in the ratio of tissues among leaves of different ages and sources. According to our study, the ratio of leaf tissues characteristic to species was neither significantly influenced by the biotop, nor by the age of the leaves. However, there is a difference in tissues size. Summarising the results, the species can be considered „only” as ecotypes on the different studied areas. Our new result is that kranz anatomy can also be found in the leaf-sheath. This research was supported by the Hungarian Scientific Fund (OTKA), grant No. T016511 and T026346.